Simultaneous imaging of neural activity in three dimensions - Quirin, Sean; Jackson, Jesse; Peterka, Darcy S.; Yuste, Rafael (Frontiers in Neural Circuits, 2014)
We introduce a scanless optical method to image neuronal activity in three dimensions simultaneously. Using a spatial light modulator and a custom-designed phase mask, we illuminate and collect light simultaneously from different focal planes and perform calcium imaging of neuronal activity in vitro and in vivo. This method, combining structured illumination with volume projection imaging, could be used as a technological platform for brain activity mapping.